USE OF RECITATION LEARNING METHOD IN DEVELOPING STUDENT'S LEARNING ABILITIES - Hanum, Ardina; Kustati , Martin; Amelia, Rezki; Gusmirawati, Gusmirawati (Media Inovasi Pendidikan dan Publikasi, 2024)
This research aims to determine the use of the recitation learning method in developing students' learning abilities in Fiqh subjects in class XI Madrasah Aliyah Negeri 2 Merangin. Methods have a significant role in teaching and learning activities. The abilities that students are expected to have will be determined by the relevance of using a method that is appropriate to the objectives. In the learning process at Madrasah Aliyah Negeri 2 Merangin there are still students who feel bored and lack focus and often talk and go in and out of class when the teacher explains the subject matter, this disrupts the learning process and the teacher cannot convey the material as a whole, resulting in motivation to learn. Students will tend to decline and find it difficult to develop their learning abilities. This research is qualitative research with data collection techniques carried out by observation, interviews and documentation. The results of the research show that the use of the recitation learning method in developing students' learning abilities in the Fiqh subject in class XI Madrasah Aliyah Negeri 2 Merangin has been effective and the benefits can be felt. This can be seen from students' activeness in class, students' level of understanding of the material, enthusiasm and enthusiasm for learning which is getting better day by day, speaking skills in front of the class which are becoming more fluent, and also daily test results which are increasing.